Study of reading habits 1989 - Jönköping - Weibull, Lennart (University of Gothenburg, 1991)
This survey forms part of the research program ´Dagspresskollegiet´. The target group of this survey was the inhabitants of Jönköping. Most of the questions are replications of questions asked in previous readership studies, i.e. questions concerning reading habits, subscriptions of papers, reading interests, and background variables such as gender, age, education and party preference. The respondent also had to compare the two local papers Jönköpings Posten and Smålands Folkblad with regard to a number of qualities. A battery of questions dealt with the local paper Smålands Folkblad specifically.

Denna undersökning ingår i forskningsprogrammet "Dagspresskollegiet". Målgruppen för denna undersökning var Jönköpings invånare. De flesta av frågorna är replikeringar av frågor som ställts i tidigare läsarstudier, det vill säga frågor om läsvanor, prenumerationer av papper, läsintressen och bakgrundsvariabler som kön, ålder, utbildning och festpreferenser. Respondenten fick också jämföra de två lokala tidningarna Jönköpings Posten och Smålands Folkblad med avseende på ett antal kvaliteter. Ett batteri av frågor behandlade specifikt den lokala tidningen Smålands Folkblad.
Läsvanestudien 1989 - Jönköping
Keywords: internal politics; inrikespolitik; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap